Ummah - Moten, Abdul Rashid (Oxford University Press, 2014)
The Arabic term ummah refers to a people or a community united by certain features that they share in common, such as customs, ethnicity, history, language, and, particularly, religion. It is often used to refer to the ummah al- Muḥammadīyah (community of Muḥammad) or ummah al-Islāmīyah (community of Islam). Although its meaning has developed throughout history, it has often been used to express the essential unity of Muslims in diverse cultural settings.